2003
DOI: 10.1177/0148607103027003208
|View full text |Cite
|
Sign up to set email alerts
|

Safety and metabolic tolerance of a concentrated long‐chain triglyceride lipid emulsion in critically ill septic and trauma patients

Abstract: Our results indicate that while both fat emulsions used in the TPN of critically ill patients are clinically safe, the 30% long-chain triglyceride fat emulsion with a phospholipid/triglyceride ratio of 0.04 causes fewer lipid metabolic disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The overall benefits to critically ill patients of balanced nutrition, which includes lipid emulsions that are generally safe, outweighs these concerns [11].…”
Section: Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall benefits to critically ill patients of balanced nutrition, which includes lipid emulsions that are generally safe, outweighs these concerns [11].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…A better understanding of hepatic fatty acid metabolism is still needed [16]. The choice of medium-or long-chain triglycerides or a combination of the two is not well defined [11,17,18], though certain patient populations may benefit from mediumchain triglycerides [19,20]. Patients should receive a minimum of 4% to 8% of calories from lipid emulsion, which is typically 50% linoleic acid .…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Jones el al originally proposed the beneficial effects of the soybean-based ILE as a myocardial energy substrate after ischemic arrest (15) and Van de Velde et al demonstrated the benefit of a systemic-infusion of ILE during recovery in several animal models of cardiac stunning (16, 17). The use of ILE during resuscitation is advantageous from a practical standpoint since ILE are readily available, clinically approved (as a parenteral nutrition supplement), easily infused, and exhibits a favorable safety profiles (1820). These clinical advantages have led to the use to ILE as an effective treatment for cardiac pharmacotoxicity (21, 22).…”
Section: Introductionmentioning
confidence: 99%
“…Practices used as precautionary methods for patients at risk of refeeding syndrome, such as replacing abnormal electrolytes, are supported by the literature (Solomon and Kirby, 1990;Crook et al, 2001). Different lipid emulsions based on different concentrations of triglyceride, fatty acids and phospholipid are available (Garcia de Lorenzo et al, 2003). A number of early studies suggested that high triglyceride emulsions suppress immunological function, thereby increasing patients' risk of infection and complications (Fischer et al, 1980;Fraser et al, 1983).…”
Section: Implementation Of Nutrition Care Planmentioning
confidence: 99%
“…A recent study found that lipid emulsions of high triglyceride concentration (30% intralipid) resulted in fewer disturbances in lipid metabolism in critically ill septic and trauma patients, compared to lipid emulsions of lower triglyceride concentration (20% intralipid) (Level II evidence) (Garcia de Lorenzo et al, 2003). The authors suggest that this may be due to the lower phospholipid/triglyceride ratio in the former emulsion, with both lipid emulsions showing similar results with respect to tolerance and safety (Garcia de Lorenzo et al, 2003).…”
Section: Implementation Of Nutrition Care Planmentioning
confidence: 99%